EXAMINING THE LEGALITY OF NIGERIA DEPOSIT INSURANCE CORPORATION AS THE INSURER OF CUSTOMERS’ DEPOSITS FROM THE PERSPECTIVE OF SHARIA - Imam-Tamim, Muhammad Kamaldeen; Salawu, Khadijah Akorede (Fakultas Syariah, 2021)
The establishment of NDIC was the government’s major policy shift from saving the banks from collapsing to saving the deposits of the depositors, and the Corporation insures both conventional and Islamic banks. However, the establishment and operational framework of this Corporation is devoid of any Islamic bias. The research work examines the legality of NDIC as an insurer of customers’ deposits within the provisions of Sharia by looking into the need for and the extent to which Islamic banks can participate in the scheme. The research is a normative research and uses a qualitative approach. This method is used to obtain the data from the sources in order to examine the legality of NDIC and its operation within Sharia as the insurer of Islamic bank deposits. The results showed that the major aim of the Corporation is in line with the Sharia but the operations enacted by some legislative frameworks are contrary to the provisions of Sharia. Some recommendations were prescribed to amend these lapses to further improve the standing of NDIC as an Insurer of the deposits of Islamic bank’s customers’, introduction of a mudarabah or musharakah arrangement where the parties involved would share the profit and loss in respect of the invested funds, and the adoption of an Islamic Deposit Insurance Scheme to ensure that Islamic Banks’ participation in DIS is fully sharia-compliant.Pembentukan NDIC merupakan perubahan kebijakan utama pemerintah untuk menyelamatkan bank dari keterpurukan. Kebijakan ini juga bertujuan menyelamatkan simpanan para deposan dan asuransi perusahaan di bank konvensional maupun syariah. Penelitian ini mengkaji legalitas NDIC sebagai penjamin simpanan nasabah dalam ketentuan syariah dengan melihat kebutuhan dan partisipasi bank syariah dalam skema tersebut. Artikel ini merupakan penelitian normatif menggunakan pendekatan kualitatif. Metode tersebut digunakan untuk memperoleh data dari sumber dan menguji legalitas NDIC serta operasionalnya sebagai penjamin simpanan bank syariah. Hasil penelitian menunjukkan bahwa tujuan utama perusahaan sejalan dengan syariah, tetapi eksekusi yang dilakukan oleh beberapa kerangka legislatif bertentangan dengan ketentuan syariah. Beberapa rekomendasi ditentukan untuk mengubah penyimpangan ini, yakni (1) meningkatkan posisi NDIC sebagai penjamin simpanan nasabah bank syariah, (2) sosialisasi akad mudarabah atau musyarakah yang memberikan aturan pada pihak-pihak terlibat untuk berbagi keuntungan dan kerugian sesuai investasi dana, dan (3) penerapan Skema Asuransi Simpanan Syariah untuk memastikan bahwa partisipasi bank syariah dalam DIS sepenuhnya sesuai syariah.